2020
DOI: 10.2147/ijgm.s269649
|View full text |Cite
|
Sign up to set email alerts
|

<p>Vertebrobasilar Dolichoectasia as a Rare Cause of Simultaneous Abducens and Vestibulocochlear Nerve Symptoms: A Case Report and Literature Review</p>

Abstract: Vertebrobasilar dolichoectasia (VBD) can lead to cranial nerve symptoms. However, multiple cranial nerve symptoms associated with VBD in one case remain extremely rare. We here present the case of a 33-year-old male with VBD diagnosed by multimodality imaging, who developed simultaneous abducens and vestibulocochlear nerve symptoms and subsequently improved after blood pressure control treatment. To our knowledge, this is the first report of such a vascular disorder resulting in simultaneous symptoms of the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…Grigoryan et al [ 7 ] reported a case with hemifacial spasm which was resulted from compression of the facial nerve by the contralateral tortuous vertebral artery. Zang et al [ 8 ] reported a case of simultaneous abducens and vestibulocochlear nerve symptoms related to vertebrobasilar dolichoectasia. Considering the limited space within the posterior fossa, the successive occurrence, although MVD had been performed 3 years prior to the onset of VP, of abducens nerve dysfunction, hemifacial spasm and VP is closely related to NVCC by the contralateral tortuous vertebral artery.…”
Section: Discussionmentioning
confidence: 99%
“…Grigoryan et al [ 7 ] reported a case with hemifacial spasm which was resulted from compression of the facial nerve by the contralateral tortuous vertebral artery. Zang et al [ 8 ] reported a case of simultaneous abducens and vestibulocochlear nerve symptoms related to vertebrobasilar dolichoectasia. Considering the limited space within the posterior fossa, the successive occurrence, although MVD had been performed 3 years prior to the onset of VP, of abducens nerve dysfunction, hemifacial spasm and VP is closely related to NVCC by the contralateral tortuous vertebral artery.…”
Section: Discussionmentioning
confidence: 99%